2008
DOI: 10.1016/j.neuroscience.2008.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of vesicular glutamate transporters 1 and 2 in the rat inferior colliculus

Abstract: The inferior colliculus is a major relay nucleus in the ascending auditory pathways that receives multiple glutamatergic inputs. Vesicular glutamate transporters 1 and 2 (VGLUT1, VGLUT2) most often have complementary non-overlapping distributions and can be used to differentiate glutamatergic inputs. The present study therefore examined co-immunolabeling of VGLUT1 and VGLUT2 in three divisions of the inferior colliculus. Additional co-immunolabeling of microtubule associated protein 2 and neuronal class III β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…The discrepancy of vGluT1 and -2 co-localization in our study and the complementary distribution of vGluT1 and -2 in the CN granule cell region observed by others may be due to species differences (guinea pig in previous studies and rat in the current study). Recently, several studies of the auditory system suggest co-production of vGluT1 and -2 in the SOC (Billups, 2005; Blaesse et al, 2005) and the IC (Altschuler et al, 2008) under normal hearing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy of vGluT1 and -2 co-localization in our study and the complementary distribution of vGluT1 and -2 in the CN granule cell region observed by others may be due to species differences (guinea pig in previous studies and rat in the current study). Recently, several studies of the auditory system suggest co-production of vGluT1 and -2 in the SOC (Billups, 2005; Blaesse et al, 2005) and the IC (Altschuler et al, 2008) under normal hearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although roles for vGluT1 and -2 in auditory brainstem plasticity have been suggested (Zhou et al, 2007; Altschuler et al, 2008; Zeng et al, 2009), vGluT3 function in this pathway has not been established. In addition to being profoundly deaf, mice with no vGluT3 expression exhibit decreased cochlear nucleus volumes and hyperexcitable neurons (Seal et al, 2008), similar to what is observed in the auditory pathways following hearing loss (Niparko and Finger, 1997; Kaltenbach and Afman, 2000; Kaltenbach et al, 2000; Mossop et al, 2000; Salvi et al, 2000; Brozoski et al, 2007; Bauer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Given that CC cells likely employ VGLUT1(Ito and Oliver 2010), it is conceivable that the lack of VGLUT1 labeling is due to a paucity CC terminals in this region. In contrast, circumferential axo-somatic VGLUT2 labeling, thought to be only on giant GABAergic tectothalamic neurons (Ito, Bishop and Oliver 2009), was seen in layer 2, not layers 1 and 3 (Altschuler et al 2008) and appears to be seen preferentially in the extramodular parts of layer 2.…”
Section: Molecular and Circuit-level Considerationsmentioning
confidence: 94%
“…Distinctly higher expression of the vesicular inhibitory amino acid transporter is found in layer 2 of the LC, a result which is consistent with studies showing GAD staining in layer 2 of the LC (Ito, Bishop and Oliver 2011). In addition, for the vesicular glutamate transporters, the labeling of VGLUT1 is densest in the DC and although less dense in the CNIC and LC (Altschuler et al 2008), the lack of labeling in layer 2 of the LC is remarkable. Given that CC cells likely employ VGLUT1(Ito and Oliver 2010), it is conceivable that the lack of VGLUT1 labeling is due to a paucity CC terminals in this region.…”
Section: Molecular and Circuit-level Considerationsmentioning
confidence: 99%
“…For example, recent studies have shown a majority of large neurons in the IC that are GABAergic (Oliver et al, 1994;Merchan et al, 2005;Hernández et al, 2006). Furthermore, the largest of these GABAergic ones also exhibit VGLUT2 axosomatic inputs (Altschuler et al, 2008;Ito et al, 2009). This is true not only for the CNIC neurons but also for the LCIC and DCIC (Ito et al, 2009) suggesting that they might correspond to the larger neurons (bitufted and chandelier types) described in the LCIC or the large multipolar neurons from the deep DCIC.…”
Section: Subdivision Boundaries Neuronal Types and Functional Signifmentioning
confidence: 94%